A Comparative Analysis of Microbe-Based Technologies Developed at ICAR-NBAIM Against Erysiphe necator Causing Powdery Mildew Disease in Grapes (Vitis vinifera L.) - Malviya, Deepti; Thosar, Ratna; Kokare, Namrata; Pawar, Shital; Singh, Udai B.; Saha, Sujoy; Rai, Jai P.; Singh, Harsh V.; Somkuwar, R. G.; Saxena, Anil K. (Frontiers in Microbiology, 2022)
Globally, Erysiphe necator causing powdery mildew disease in grapevines (Vitis vinifera L.) is the second most important endemic disease, causing huge economic losses every year. At present, the management of powdery mildew in grapes is largely dependent upon the use of chemical fungicides. Grapes are being considered as one of the high pesticide-demanding crops. Looking at the residual impact of toxic chemical pesticides on the environment, animal, and human health, microbe-based strategies for control of powdery mildew is an emerging technique. It offers an environment-friendly, residue-free, and effective yet safer approach to control powdery mildew disease in grapes. The mode of action is relatively diverse as well as specific to different pathosystems. Hence, the aim of this study was to evaluate the microbe-based technologies, i.e., Eco-pesticide®, Bio-Pulse®, and Bio-Care 24® developed at the Plant-Microbe Interaction and Rhizosphere Biology Lab, ICAR-NBAIM, Kushmaur, against grape powdery mildew and to integrate these technologies with a safer fungicide (sulfur) to achieve better disease control under organic systems of viticulture. The experiments were conducted at four different locations, namely, the vineyards of ICAR-NRCG, Rajya Draksha Bagayatdar Sangh (MRDBS), and two farmers' fields at Narayangaon and Junnar in the Pune district of Maharashtra. A significantly lower percent disease index (PDI) was recorded on the leaves of grape plants treated with Eco-Pesticide®/sulfur (22.37) followed by Bio-Pulse®/sulfur (22.62) and Bio-Care 24®/sulfur (24.62) at NRCG. A similar trend was observed with the lowest PDI on bunches of Eco-pesticide®/sulfur-treated plants (24.71) followed by Bio-Pulse®/sulfur (24.94) and Bio-Care®/sulfur (26.77). The application of microbial inoculants singly or in combination with sulfur has a significant positive impact on the qualitative parameters such as pH, total soluble solids (TSS), acidity, berry diameter, and berry length of the grapes at different locations. Among all the treatments, the Bio-Pulse®/sulfur treatment showed the highest yield per vine (15.02 kg), which was on par with the treatment Eco-Pesticide®/sulfur (14.94). When compared with the yield obtained from the untreated control, 2.5 to 3 times more yield was recorded in the plants treated with either of the biopesticides used in combination with sulfur. Even in the case of individual inoculation, the yield per vine was approximately two times higher than the untreated control and water-treated plants across the test locations. Results suggested that microbial technologies not only protect grapevines from powdery mildew but also enhance the quality parameters with increased yield across the test locations.